Population structure change in a temperate reef coral after a quarter of century. (5th June 2022) - Azzola, Annalisa; Bianchi, Carlo Nike; Morri, Carla; Oprandi, Alice; Peirano, Andrea; Montefalcone, Monica
Abstract: Seawater warming is affecting corals worldwide. Mass mortality events are increasingly frequent, and the bioconstruction potential of coral reefs is jeopardized. Revisiting sites surveyed in the past may represent a valuable tool to better understand the health state and ongoing trend of coral reefs. In the Mediterranean Sea the only reef-building coral is the endemic species Cladocora caespitosa . Several mortality events of this coral, due to thermal anomalies, have been reported in the last decades. An impressive change occurred in a population of C. caespitosa revisited 25 years after: smaller colonies became the prevalent size class and larger colonies disappeared, highlighting a loss in the bioconstruction potential. Data collected on C. caespitosa colonies in the Eastern Ligurian Sea (NW Mediterranean) revealed that mortality rate was correlated with colony size, while reproductive potential apparently increased, suggesting hormesis (i.e., enhanced reproductive output under pre-lethal conditions). Highlights: Cladocora caespitosa is the only reef-building coral in the Mediterranean Sea. C. caespitosa has been affected by mass mortality events due to the water warming. Evaluation of the present coral health status requires long-term data series. A loss in the bioconstruction potential of C. caespitosa was observed. Mortality of C. caespitosa concerns predominantly largest colonies.